Unification Theories: Means and Generalized Euler Formulas - Radu Iordanescu; Florin Felix Nichita; Ovidiu Pasarescu (Axioms, 2020)
The main concepts in this paper are the means and Euler type formulas; the generalized mean which incorporates the harmonic mean, the geometric mean, the arithmetic mean, and the quadratic mean can be further generalized. Results on the Euler’s formula, the (modified) Yang–Baxter equation, coalgebra structures, and non-associative structures are also included in the current paper.